Nanoparticles in biomedical applications - McNamara, Karrina; Tofail, Syed A. M. (Advances in physics: X, 2017)
Nanoparticles are defined as solid colloidal particles ranging in size from 10 to 1000 nm. Nanoparticles offer many benefits to larger particles such as increased surface-to-volume ratio and increased magnetic properties. Over the last few years, there has been a steadily growing interest in using nanoparticles in different biomedical applications such as targeted drug delivery, hyperthermia, photoablation therapy, bioimaging and biosensors. Iron oxide nanoparticles have dominated applications, such as drug delivery, hyperthermia, bioimaging, cell labelling and gene delivery, because of their excellent properties such as chemical stability, non-toxicity, biocompatibility, high saturation magnetisation and high magnetic susceptibility. In this review, nanoparticles will be classified into four different nanosystems metallic nanoparticles, bimetallic or alloy nanoparticles, metal oxide nanoparticles and magnetic nanoparticles. This review investigates the use of nanosystems other than iron oxide nanoparticles such as metallic nanoparticles like gold (Au) and silver (Ag), bimetallic nanoparticles like iron cobalt (Fe-Co) and iron platinum (Fe-Pt) and metal oxides including titanium dioxide (TiO 2 ) cerium dioxide (CeO 2 ), silica (SiO 2 ) and zinc oxide (ZnO) with a focus on the lesser studied nanoparticles such as silver (Ag), iron-platinum (Fe-Pt) and titanium dioxide (TiO 2 ) and how their unique properties allow for their potential use in various biomedical applications.